The practice of traditional rituals in Naga Aradhana (snake worship): a case study on Aadimoolam Vetticode Sree Nagarajaswami Temple in Kerala, India - Das, Dinu; Balasubramanian, Arumugam (2017)
Snakes are worshiped in different parts of the world based on the culture and traditions.Snake worship is a part of Hindu religion and plays an important role in cultural as well as in ritual aspect in India.This study explores the ritual practices in Naga aradhana in the Indian state Kerala, by taking Aadimoolam Vetticode Sree Nagarajaswami temple as a case study.This paper aims to understand the importance of Naga aaradhana and the practice of rituals related to Naga Dosha (curse of snakes), like Kalamezhuthu, Pulluvanpaatu, Sarpamthulal , Sarpabali, the annual festival Ayilyam Mahotsavam and the importance of Sarpakaavu (sacred groove) in the temple.This research is conducted using the methodology of personal interviews and video analysis.This study concludes that the Sarpakavu has a unique meaning and believers from different caste and religion have respect and admiration for this divinity.